Morphology and phylogeny of Tamhinispora srinivasanii sp. nov. (Tubeufiaceae) from northern Western Ghats, India - Rajeshkumar, Kunhiraman C.; Bhat, D. Jayarama; Lad, Sneha S.; Wijayawardene, Nalin W.; Singh, Sanjay K.; Pandkar, Madhura R.; Maurya, Deepak K.; Ashtekar, Nikhil D.; Hyde, Kevin D. (Phytotaxa, 2018)
In this paper we introduce a new species of Tamhinispora collected from Western Ghats of Maharashtra, India. This monotypic genus, belonging to Tubeufiaceae, was established based on the type species T. indica, collected from Tamhini Ghats of western India. The new species differs from the type species based on key characteristics, such as branched or Y-shaped conidial body and presence of arm-like conidial appendages. Single conidial cultures were developed and sporulation was established on MEA media following a long period of incubation. Phylogenetic analyses using ITS and LSU sequence data confirmed the position of T. srinivasanii along with T. indica in the Tamhinispora clade in Tubeufiaceae.